Knowledge-based economy: wealth owners portfolio choices and financialisation. A wealth supply analysis - Valente, Riccardo (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Based on a data and literature analysis as well as autonomous theoretical reasoning and argumentation by the author, the present article discusses the relevance of financialisation and portfolio choice changes under the present phase of development of modern economies. Relying upon the earlier studies by the author which stress that knowledge-based economy can be characterised as a low profitability of investment in physical capital, higher income inequalities, lower physical capital and economic growth rate phase of the development of economic systems, the present work provides variously conceived arguments to support the idea that significant portfolio choice changes by wealth owners are a relevant feature of knowledge-based economy. Some of the implications of the economic theory of the availability of assets other than physical capital and other assets more connected with production needs were thus discussed, pointing out that this leads mainly to the negation of the necessary arrival of mainstream counterbalance mechanisms which support the affirmation of higher physical capital accumulation when higher income inequalities are recorded.

Na podstawie zarówno analizy danych, literatury naukowej, jak i samodzielnie opracowanej przez autora argumentacji i rozumowania teoretycznego, artykuł analizuje ważną rolę finansyzacji i zmian w doborze oraz optymalizacji portfelowej w obecnej fazie rozwoju współczesnych gospodarek. W oparciu o wyniki wcześniejszych badań autora, z których wynikało, iż obecną fazę rozwoju można scharakteryzować jako okres niskiej opłacalności akumulacji kapitału fizycznego, wysokich nierówności w podziale dochodu, niskiego wzrostu gospodarczego i spowolnionej akumulacji kapitału, niniejsza praca przedstawia argumenty różnego pochodzenia, które popierają pogląd, iż znacząca realokacja portfelowa podejmowana przez posiadaczy majątku jest ważną cechą gospodarki opartej na wiedzy. Przedstawiono niektóre z implikacji związane z teorią ekonomiczną, jakie wynikają z dostępności aktywów różnych od kapitału fizycznego i innych aktywów bardziej związanych z potrzebami produkcyjnymi, podkreślając przy tym, że prowadzi to do negacji koniecznego pojawienia się automatycznych, równoważących mechanizmów, popieranych przez teorię neoklasyczną, na podstawie których pojawienie się wyższych nierówności w podziale dochodu prowadziłoby do występowania większej akumulacji kapitału fizycznego.
Keywords: Keynesian theory; income distribution; financialization; knowledge-based economy; economic growth; teoria Keynesowska; podział dochodu; finansyzacja; gospodarka oparta na wiedzy; wzrost gospodarczy